Multidisciplinary Treatment for Colorectal Peritoneal Metastases: Review of the Literature - Shaobo Mo; Guoxiang Cai (Gastroenterology Research and Practice)
Peritoneum is one of the common sites of metastasis in advanced stage colorectal cancer patients. Colorectal cancer patients with peritoneal metastases (PM) are traditionally believed to have poor prognosis, which indicates it is of no value to adopt surgical treatment. With the advancement of surgical techniques, hyperthermic intraperitoneal chemotherapy (HIPEC), and multidisciplinary treatment in recent years, the cognition and treatment strategies of colorectal peritoneal metastases (CPM) have changed dramatically. In terms of prognosis, CPM under the palliative systemic treatment shows an inferior outcome compared with nonperitoneal metastasis. Nevertheless, some CPM patients amenable to the complete peritoneal cytoreductive surgery (CRS) combined with HIPEC may achieve long-term survival. The prognostic factors of CPM comprise peritoneal carcinomatosis index (PCI), completeness of cytoreduction score (CC score), the presence of extraperitoneal metastasis (liver, etc.), Peritoneal Surface Disease Severity Score (PSDSS), Japanese peritoneal staging, and so forth. Taken together, literature data suggest that a multimodality approach combining complete peritoneal CRS plus HIPEC, systemic chemotherapy, and targeted therapy may be the best treatment option for PM from colorectal cancer.